ANALISIS PENGARUH KINERJA JEMBATAN TIMBANG TERHADAP KINERJA PERKERASAN DAN UMUR RENCANA JALAN (Studi Kasus Jembatan Timbang Salam, Magelang) - Arief Fath Atiya; Okty Diana Wulan Sari; Djoko Purwanto; Bagus Hario Setiadji (Jurnal Karya Teknik Sipil, 2014)
On Keprekan Road – Yogyakarta’s Limit is always crossed by heavy vehicles and sometimes overloaded. On that road found “Jembatan Timbang Salam”. Because of  still many phenomena the overloaded vehicles so that “Jembatan Timbang Salam” needs to be revisited its performance in dealing with violations of overloaded that will be effected the pavement performance. From the results of evaluation and analysis carried out, "Jembatan Timbang Salam" in category C which means its performance is in bad condition and it affects the performance of the existing pavement. Using the assumption of the initial design serviceability index (P0) 3.9, the design terminal service ability index (Pt) 2.5, Structural Number 5, and 10 years plan (2005-2015), overloaded that occurs in the field due to condition A (actual load), age of road performance only lasted for 9.48 years for the first analysis (using a growth rate for all classes of vehicles) and only lasted for 9.53 years for second analysis (using the growth rate for each type of vehicle class). Moreover there is also a decreasing road service ability index with an average decline for the first analysis due to standard JBI  load are 1.40% and due to condition A are 1.48%. And than, for the second analysis due to standard load average decline reached 3.07% and for condition A average decline reached 3.33%.But with the overlay in 2011, 2012 and 2013, the service ability index of the road are being increase. For the first analysis the increase reached 26.02% and 35.30% increasing for second analysis.